QUALITY OF INITIAL TEACHER EDUCATION: REFLECTIONS ON WHAT IS BEING RESEARCHED - Josimar de Aparecido Vieira (Editora da Universidade de Santa Cruz do Sul, 2009)
This work is discussed, in general, the state of knowledge on research dealing with the quality of the initial training of teachers. Presents an analytical and critical reading of the situation of the quality of the initial training of teachers from the analysis of the theoretical bases produced in the last decade. For this, initially, are presented some considerations on the development of this process, followed by an analysis on the issue of training. Following are considered some of the dilemmas or problems that have been addressed in the study area, suggesting mechanisms or alternative solutions. The main source of data used is the Bank of the CAPES Theses which is available on the home page http://servicos.capes.gov.br/capesdw/, for the period from 2004 until 2006. Was used to search by typing the words "initial teacher training" in the "subject", which in 2004 were examined 33 abstracts were selected and these 15, in 2005 were examined 42 abstracts, of which 07 were deployed in 2006 and were seen 44 abstracts of which 21 have been considered because they relate to the quality of initial teacher education. Involved in this analysis, this study points out some principles and data that can help with the process of initial teacher training, pointing to possible review some indicators of pedagogical projects of degree courses. Emphasizes that the specificity and multidimensionality of the performance of the teacher raises the formulation of a set of information relevant to the qualification of objectives and practices of the initial key step in the process of learning to teach. Key words: Quality of education, initial training, university education, state of knowledge; indicators.